2004
DOI: 10.1097/00005537-200408000-00031
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Anterior Commissure Involvement on Local Control of Early Glottic Carcinoma Treated by Laser Microresection

Abstract: This study shows the effectiveness of laser microsurgery for early glottic carcinoma regardless of anterior commissure involvement at presentation. This method can be performed as an outpatient procedure, even when conducting reresections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
152
1
9

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(176 citation statements)
references
References 40 publications
(67 reference statements)
14
152
1
9
Order By: Relevance
“…Stage wise these were 1/14 T2, 2/12 T3, and 1/4 T4 tumors. In another study, it was seen that T1b or T2b tumors had increased local recurrence rates compared with T1a tumors [13]. In our study, we observed that one patient with T1b, one patient with T2, and two patients with T3 had recurrence.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Stage wise these were 1/14 T2, 2/12 T3, and 1/4 T4 tumors. In another study, it was seen that T1b or T2b tumors had increased local recurrence rates compared with T1a tumors [13]. In our study, we observed that one patient with T1b, one patient with T2, and two patients with T3 had recurrence.…”
Section: Discussionsupporting
confidence: 62%
“…In our study, we observed that one patient with T1b, one patient with T2, and two patients with T3 had recurrence. Although, the number of patients in our study was small, our findings together with those of earlier studies suggest that extensive lesions in the A-com may have an increased propensity for recurrence after laser microsurgery [12,13,19]. These patients may therefore require careful surveillance for early detection of recurrence after laser microsurgery.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Steiner et al 28 analyzed the influence of anterior commissure involvement on local recurrences, laryngeal preservation, and survival in 263 patients with early glottic cancer that underwent transoral laser microsurgery. It was shown that involvement of the anterior commissure affected the local control and organ preservation rates but not the survival rates.…”
Section: The Anterior Cmmissurementioning
confidence: 99%
“…Actualmente, hay reportes de la escuela alemana (Steiner) incluso del tratamiento satisfactorio de tumores en etapas avanzadas en carcinomas glóticos, supraglóticos, de cavidad oral e hipofaringe con resultados oncológicos comparables a las modalidades convencionales en un grupo seleccionado de pacientes. En estos estudios, se afirma que la selección de los pacientes es fundamental pues se debe obtener una buena visualización de la lesión tumoral vía transoral para plantear este tipo de tratamiento [7][8][9][10][11] . El uso del láser en carcinoma laríngeo fue descrito desde 1975 por Strong como el méto-do de elección de la exéresis de los T1.…”
Section: Patologías Con Indicaciones De Cirugía Láserunclassified